Dorsal or Volar Plate Fixation of the Distal Radius: Does the Complication Rate Help Us to Choose? - Disseldorp, D.J.G.; Hannemann, P.F.W.; Poeze, M.; Brink, P.R.G. (Journal of Wrist Surgery, 2016)
Background Internal fixation with plates is a reliable fixation technique for the treatment of distal radius fractures. An ongoing discussion exists whether volar or dorsal plating is the appropriate technique. In clinical practice, volar plate fixation is usually preferred because of the assumed lower complication frequency. However, recent studies with the newer generation low-profile dorsal plates reported lower complication rates.Purpose The aim of our study was to evaluate the differences in complication rates between volar and dorsal plate for the treatment of distal radius fractures in adult patients.Patients and Methods A total of 214 patients with acute distal radius fractures were included in this retrospective study with a minimum 2 years of follow-up. In total, 123 patients were treated with dorsal plate fixation and 91 patients with volar plate fixation. Our primary study outcome was complication rate.Results The overall risk for complications was 15.4% in the dorsal group and 14.3% in the volar group (p = 0.81). A total of 19 patients had implant removal due to complications: 11 patients in the dorsal group and 8 patients in the volar group (p = 0.97).Conclusion There is no preferred plate fixation technique based on these study results. In our opinion, decision for type of plate fixation should be based on fracture type and surgeon's experience with the specific approach and plate types.Level of Evidence Therapeutic level III.
Keywords: distal radius fractures; internal fixation; dorsal plates; volar plates; complications